Mean Platelet Volume and Testicular Torsion: New Findings - Peretti, Marta; Zampieri, Nicola; Bertozzi, Mirko; Bianchi, Federica; Patanè, Simone; Spigo, Valentina; Camoglio, Francesco S. (Urology Journal, 2019)
Introduction: Testicular torsion is an emergency at any age; the aim of this study is to evaluate the role of mean platelet volume to assess the viability of the testes before surgery Materials and methods: We retrospectively analysed the medical records of consecutive patients who underwent surgical exploration for acute scrotal pathology between January 2014 and December 2016 in our institution. Patients: were divided into two groups (detorsion of testes and orchyectomy); a third group was created as control group. All patients underwent blood exam before surgery; inclusion and exclusion criteria were created. We also evaluated the association between mean platelets volume and the testicular recovery during surgery Result: After reviewing medical charts following the inclusion and exclusion criteria, 8 patients were enrolled in Group 1 and 11 patients in Group 2. 33 healthy controls were enrolled in Group 3. MPV value in Group 1 resulted significantly different (p < 0.01) from the value in Group 2 and 3. The duration of symptoms was shorter than 6 hours in 4/8 (50%) patients in Group 1; this early referral to hospital allowed prompt detorsion and testicular recovery. In these “early-presenting” patients, MPV value was significantly lower than in patients with torsion of testicular appendage (p = 0.01) and in controls (p = 0.001). Conclusion: MPV could be a useful adjunct in diagnosing TT, aiding its differential diagnosis with Torsion of the testicular appendage. The lower MPV value in “early-presenting” patients with TT suggests a role in predicting the testis viability, and therefore the appropriate treatment.